Coastline dynamics and its influence on community activities at Tanjong Lobang Beach, Miri, Sarawak - Jonathan Lavung; Adi Jafar; Mohammad Tahir Mapa; Listyo Yudha Irawan (UTHM, 2024)
Coastal areas are important especially for the tourism sector which involves recreational and business activities. However, the phenomenon of shoreline change has the potential to jeopardize the welfare of local communities, including the aspect of economic disruption. Tangible effects can be seen through the destruction of infrastructure, loss of land and destruction of vegetation. Pantai Tanjong Lobang located in Miri, Sarawak is an area that has experienced significant shoreline change. Therefore, this study aims to identify the extent of shoreline change in Tanjong Lobang, Miri, Sarawak while analyzing its impact on the socioeconomic activities of communities in the area. Shoreline changes were analyzed using Geographic Information System (GIS) software by comparing the shoreline position of remote sensing images (Google Earth Pro) in 2001, 2013 and 2023. To identify the impact of shoreline, change on community activities, a survey method was used. The results of the study found that in a period of 22 years (2001 to 2023) there was a change in the shoreline with 22 meters towards the coastal land. This change is indirectly found to have jeopardized the safety and comfort of visitors in carrying out their recreational activities in the beach area. Identification of coastal areas at risk of experiencing shoreline changes needs to be done so that the community and local authorities are willing to face these changes.